Answered

Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

help and explain ///////////////////////////

Help And Explain class=

Sagot :

caylus

Hello,

First, you must understand that

(f-g)(x) means f(x)-g(x) it is the difference of two functions :

f(x)=2x+4 and g(x)=3x-7

f(5)=2*5+4=10+4=14

g(5)=3*5-7=15-7=8

So, (f-g)(5)= f(5)-g(5)=14-8=6

Answer A: none of the choices are correct.

An other way to do it:

(f-g)(x)=f(x)-g(x)=2x+4-(3x-7)= 2x-3x+4+7=-x+11

if x= 5 then (f-g)(5)=-5+11=6

Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.